Financial contracts as coordination device - Chloé Le Coq; Sebastian Schwenen (Journal of Economics & Management Strategy, 2020)
We study the use of financial contracts as bid-coordinating device in multi-unit uniform price auctions. Coordination is required whenever firms face a volunteer's dilemma in pricing strategies: one firm (the “volunteer") is needed to increase the market clearing price. Volunteering, however, is costly, as inframarginal suppliers sell their entire capacity whereas the volunteer only sells residual demand. We identify conditions under which signing financial contracts solves this dilemma. We test our framework exploiting data on contract positions by large producers in the New York power market. Using a Monte Carlo simulation, we show that the contracting strategy is payoff dominant and provide estimates of the benefits of such strategy.
Keywords: 330; auctions; coordination; electricity; forward markets; volunteer's dilemma